Adsorptive removal of methylene blue and acid orange 10 dyes from aqueous solutions using oil palm wastes-derived activated carbons - Baloo, L. (Elsevier B.V., 2021)
Presence of toxic dyes in industrial wastewaters deteriorates the environment. Wastewater pollution control using locally obtainable agricultural by-products could be an eco-friendly and sustainable strategy. Efficiencies of activated carbons (AC) developed from empty fruit bunches (EFB) and mesocarp fibers (MF) of oil palm were evaluated in methylene blue (MB) and Acid orange 10 (AO10) dyes removal. Impacts of operational parameters including adsorbent dose, pH, initial concentration of dyes, and contact time were examined on dyes adsorption. Maximum adsorption values of MB (24.00 mg/g) and AO10 (18.76 mg/g) were achieved at pH 2 and 3, respectively, 50 mg/L initial dyes concentration, adsorbents dosage of 5 g/L, and 90 min contact time. Evaluation of adsorption isotherms revealed that the Freundlich model provided the best fit to the empirical data (R2 â¥ 0.692). MB isotherm through MF, however, was better represented by Langmuir model (R2 = 0.979). MF activated carbon showed higher capacity in immobilization of both dyes probably due to its larger surface area (552.72 m2/g) and porosity (0.4458 cm3/g). Dye adsorption on to the activated carbons go along with pseudo-second order kinetic model. Â© 2021 THE AUTHORS